Penerapan Model Log-Logistik Proporsional Hazard Untuk Menentukan Faktor yang Mempengaruhi Kondisi Financial Distress - Sudarno, Sudarno; I Maruddani, Di Asih (Universitas Sebelas Maret, 2023)
Every company is likely to experience an up or down phase in its financial performance. A decline in financial performance is a condition of financial distress. Financial distress is an event of a continuous decline in a company's financial performance over a certain period of time. The variables in this research are the response variable in the form of the time of company experiences financial distress, while the covariates are the solvency ratio, liquidity ratio, growth ratio, profitability ratio, company size and activity ratio. The aim and objective of the research is to obtain the property and significance of covariates when a company experiences financial distress. How to determine covariates that are significant to financial distress. The model used is a log-logistic proportional hazard regression model. The log-logistic model is a regression model in the form of a maximum extreme function with right asymptotics and non-negative random variables, while the Cox proportional hazards model is a survival model with the independent variables being time and covariates, between time and covariates being independent. The results of this research are that companies in the infrastructure, utilities and transportation sectors experience financial distress, influenced by solvency ratios, liquidity ratios and profitability ratios. The solvency ratio and profitability ratio have a positive effect, while the liquidity ratio has a negative effect on the timing of financial distress. The contribution of these factors to companies experiencing financial distress is 1.1% (for liquidity ratio), 3.4% (for solvency ratio), and 95.5% (for profitability ratio).Keywords: financial distress; log-logistic; portional hazard; profitability ratio